Stress Assessment of Vestibular Endurance Training for Civil Aviation Flight Students Based on EEG - Hu, Haixu; Fang, Zhou; Qian, Zhiyu; Yao, Liuye; Tao, Ling; Qin, Bing (Frontiers in Human Neuroscience, 2021)
3 Objective: The main goal of our study is to clarify the EEG characteristics of the stress response 4 caused by vestibular endurance training under the real conditions. 5 Methods: Ten pilot trainees received a series of acute anti-vertigo training stimulations on 6 the rotary ladder while recording electroencephalographic data (64 electrodes).Afterwards,the 7 subject’s anti-vertigo ability was tested for the best performance after 1 month of training, and 8 verifying whether it is relating to the EEG signals we collected before. 9 Results: (1) The absolute power of α waves in the C3 and C4 regions is same as the difference 10 between 1 min before and 2 min after stimulation, and their activity is enhanced by stimulation. 11 Otherwise, the activation of the C3 region after 5min of stimulation is still significant changed. 12 (2) Discover a spearman rank correlation, the α waves in the C3 and C4 the greater the power 13 change, the better the performance of the subject in the proficient stage. 14 Conclusions: C3 and C4 areas are specific brain regions of the stress response of anti-vertigo 15 endurance training, and the absolute power of the α wave can be used as a parameter for 16 identifying the degree of motion sickness(MS). The absolute power changes of α waves in the C3 17 and C4 areas are positively correlated with their anti-vertigo potential. 18 Significance: The increasing of the absolute power of α wave in the C3 and C4 is a manifestation 19 of MS stress adaptability.